2022
DOI: 10.1155/2022/5728991
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors of Recurrent Stroke in Young and Middle-Aged Stroke Patients after Interventional Therapy

Abstract: Objective. To explore the risk factors of recurrent stroke in young and middle-aged stroke patients after interventional therapy. Methods. Retrospective analysis was conducted on the data of 300 young and middle-aged stroke patients treated in our hospital (February 2015–February 2017). All patients received interventional therapy. They were followed up continuously after the interventional therapy, with recurrent stroke as the only endpoint event, and those who did not have the endpoint events were followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Risk factors of Recurrent Stroke in Young and Middle-Aged Stroke Patients After Interventional Therapy” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Risk factors of Recurrent Stroke in Young and Middle-Aged Stroke Patients After Interventional Therapy” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled "Risk factors of Recurrent Stroke in Young and Middle-Aged Stroke Patients After Interventional Therapy" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%